Corruption under Austerity - Gianmarco Daniele; Tommaso Giommoni (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We study how policies limiting the spending capacity of local governments may reduce corruption. We exploit the extension of one such policy, the Domestic Stability Pact (DSP), to small Italian municipalities. The DSP led to a decrease in both recorded corruption rates and corruption charges per euro spent. This effect emerges only in areas in which the DSP put a binding cap on municipal capital expenditures. The reduction in corruption is linked to accountability incentives as it emerges mostly in pre-electoral years and for re-eligible mayors. We then estimate the impact of the extension of the DSP on local public good provision in the following years, finding a null effect in the short run. Overall, our findings suggest that budget constraints might induce local governments to curb expenditures in a way that dampens their exposure to corruption without depressing local welfare.
Keywords: D72; D73; H62; H72; K34; 330; corruption; austerity; fiscal rules; European funds; local public finance; public procurement